Solid electrolyte and battery

By using a solid electrolyte composed of polyurethane sulfide and polyacrylonitrile, the brittleness and warping problems of polymer solid electrolytes are solved, improving the battery's flexibility, mechanical properties and ionic conductivity, and enhancing the battery's safety and cycle performance.

CN121123390AActive Publication Date: 2025-12-12SHENZHEN HAODYNE TECH CO LTD

Patent Information

Application Number
CN202511613931.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2025-12-12
Estimated Expiration
2045-11-06

AI Technical Summary

Technical Problem

Existing polymer solid electrolytes suffer from excessive brittleness and warping, which affects the battery manufacturing process. They also exhibit low ionic conductivity and mechanical properties.

Method used

A solid electrolyte composed of polyurethane, polyacrylonitrile, and lithium salt is used. Through hydrogen bonding between the thiourethane structural units in polyurethane and polyacrylonitrile, the polymer forms hydrogen bonds, resulting in good compatibility, reducing the crystallinity of polyacrylonitrile, improving flexibility and mechanical properties, and promoting lithium-ion transport through sulfur atoms, thereby improving ionic conductivity.

Benefits of technology

It achieves high ionic conductivity and good mechanical properties, suppresses lithium dendrite puncture, and improves battery safety and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a solid electrolyte and a battery. The solid electrolyte comprises polythionocarbamate, polyacrylonitrile and a lithium salt, wherein the polythionocarbamate comprises a thiocarbamate structural unit. In the solid electrolyte provided by the invention, amino groups in a thiocarbamate structural unit in the polythionocarbamate and cyano groups in polyacrylonitrile form hydrogen bonds, so that the polythionocarbamate and the cyano groups in the polyacrylonitrile have good compatibility, the crystallinity of the polyacrylonitrile can be effectively reduced by blending the polythionocarbamate and the polyacrylonitrile, and the flexibility of the solid electrolyte is improved; and meanwhile, the solid electrolyte has relatively good mechanical properties. Particularly, sulfur atoms in a thiocarbamate structural unit in the polythionocarbamate contribute to promoting lithium ion transmission and improving the ionic conductivity, and due to the interaction of hydrogen bonds formed by the polythionocarbamate and polyacrylonitrile, the transmission rate of lithium ions can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of batteries, and particularly relates to a solid-state electrolyte and a battery. BACKGROUND

[0002] Since commercialization, lithium ion batteries have been widely used in the fields of portable electronic devices and electric vehicles. Unlike traditional liquid lithium ion batteries, all-solid-state lithium batteries have the advantages of high specific energy, high safety performance, long cycle life, etc., and have become a research and development hotspot in the field of new chemical batteries in recent years.

[0003] The solid-state electrolyte includes a polymer solid-state electrolyte. Although the ionic conductivity of some polymer electrolytes in the existing polymer solid-state electrolyte can meet the use requirements of the solid-state electrolyte, the polymer electrolyte has the problem of too strong brittleness and accompanying warping, which affects the subsequent processing process of the battery.

[0004] Therefore, it is urgent to provide a solid-state electrolyte with mechanical properties and high ionic conductivity. SUMMARY

[0005] In view of the technical problem of low ionic conductivity and mechanical property of the existing solid-state electrolyte, the application provides a solid-state electrolyte and a battery.

[0006] To solve the above technical problem, on the one hand, the application provides a solid-state electrolyte, which comprises a polythiourethane, a polyacrylonitrile and a lithium salt, and the polythiourethane comprises a thiourethane structural unit.

[0007] Preferably, the solid-state electrolyte comprises 20%-40% of the polythiourethane, 40%-60% of the polyacrylonitrile and 20%-40% of the lithium salt, based on the total mass of the solid-state electrolyte being 100%.

[0008] Preferably, the glass transition temperature of the polythiourethane is 40℃-80℃.

[0009] Preferably, the weight average molecular weight of the polythiourethane is 10x10 4 g / mol-20x10 4 g / mol.

[0010] Preferably, the weight average molecular weight of the polyacrylonitrile is 20x10 4 g / mol-40x10 4 g / mol.

[0011] Preferably, the polythiourethane comprises a polymer formed by the participation of a diisocyanate compound and a thiol compound in polymerization.

[0012] Preferably, the molar ratio of the isocyanate groups of the diisocyanate compound and the mercapto groups of the thiol compound is 1:0.95-1:1.1.

[0013] Preferably, the diisocyanate compound comprises at least one of toluene diisocyanate, diphenyl methane diisocyanate, dicyclohexyl methane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate.

[0014] Preferably, the thiol compound comprises at least one of ethylene glycol bis-mercaptoacetate, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetra(3-mercaptopropionate), myo-inositol hexa(mercaptopropionate), and polythiol Capcure 3800.

[0015] Preferably, the lithium salt comprises at least one of lithium bistrifluoromethylsulfonimide, lithium hexafluorophosphate, lithium bisfluorosulfonylimide, lithium perchlorate, lithium tetrafluorophosphate, lithium difluorophosphate, lithium bisoxalate borate, and lithium difluoro oxalate borate.

[0016] In another aspect, the present application provides a battery comprising a solid-state electrolyte film, wherein the solid-state electrolyte film comprises the solid-state electrolyte according to any one of the above.

[0017] Preferably, the thickness of the solid-state electrolyte film is 50 μm-200 μm.

[0018] In the solid-state electrolyte provided by the present application, the amino group in the thiourethane structure unit and the cyano group in the polyacrylonitrile form hydrogen bonds, so that the two have good compatibility. The blending of the polythiourethane and the polyacrylonitrile can effectively reduce the crystallinity of the polyacrylonitrile, improve the flexibility of the solid-state electrolyte, and at the same time make the solid-state electrolyte have good mechanical properties. In particular, the sulfur atom in the thiourethane structure unit can help to promote the transmission of lithium ions, improve the ionic conductivity, and further improve the transmission rate of lithium ions and the cycle performance of the battery due to the interaction of the hydrogen bonds formed by the polythiourethane and the polyacrylonitrile. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects solved by the present application more clearly understood, the present application will be further described in detail below with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and not used to limit the present application.

[0020] An embodiment of the present application provides a solid-state electrolyte, comprising a polythiourethane, a polyacrylonitrile and a lithium salt, wherein the polythiourethane comprises a thiourethane structure unit.

[0021] The amino group in the thio urethane structural unit in the polythio urethane and the cyano group in the polyacrylonitrile form a hydrogen bond in the solid-state electrolyte provided by the embodiment, so that the two have good compatibility. Blending the polythio urethane and the polyacrylonitrile can effectively reduce the crystallinity of the polyacrylonitrile, improve the flexibility of the solid-state electrolyte, and at the same time make the solid-state electrolyte have good mechanical properties. In particular, the sulfur atom in the thio urethane structural unit in the polythio urethane helps to promote lithium ion transmission and improve ionic conductivity, and thanks to the interaction of the hydrogen bond formed by the polythio urethane and the polyacrylonitrile, the transmission rate of lithium ions can be further improved, and the cycle performance of the battery can be improved.

[0022] In some embodiments, the solid-state electrolyte includes 20%-40% of the polythio urethane, 40%-60% of the polyacrylonitrile, and 20%-40% of the lithium salt, based on the total mass of the solid-state electrolyte being 100%.

[0023] By limiting the mass content of the polythio urethane, the polyacrylonitrile, and the lithium salt within the above range, the solid-state electrolyte has good flexibility and mechanical properties at the same time, and has high ionic conductivity. If the content of the polythio urethane is lower than the range, the flexibility of the solid-state electrolyte cannot be effectively improved, and at the same time, the transmission rate of lithium ions is reduced, and the ionic conductivity of the solid-state electrolyte is reduced. If the content of the solid-state electrolyte is higher than the range, the mechanical properties of the solid-state electrolyte are reduced, the penetration of lithium dendrites cannot be effectively inhibited, and the safety performance of the battery is affected.

[0024] Specifically, the mass content of the polythio urethane includes but is not limited to 20%, 23%, 26%, 29%, 32%, 35%, 38%, or 40%.

[0025] The mass content of the polyacrylonitrile includes but is not limited to 40%, 43%, 46%, 49%, 52%, 55%, 58%, or 60%.

[0026] The mass content of the lithium salt includes but is not limited to 20%, 23%, 26%, 29%, 32%, 35%, 38%, or 40%.

[0027] In some embodiments, the glass transition temperature Tg of the polythio urethane is 40-80℃. By limiting the glass transition temperature of the polythio urethane within the above range, the mechanical strength of the solid-state electrolyte film formed by the solid-state electrolyte can inhibit the penetration of lithium dendrites, and improve the safety performance of the battery.

[0028] The glass transition temperature is obtained by differential thermal analysis.

[0029] In some embodiments, the weight average molecular weight Mw of the polythio urethane is 10×10 4 -20×10 4g / mol. By limiting the weight average molecular weight of the polythiourethane to be within the above range, the glass transition temperature of the polythiourethane is controlled to meet the requirement of 40-80°C.

[0030] Specifically, the weight average molecular weight of the polythiourethane includes but is not limited to 10 x 10 4 g / mol, 11 x 10 4 g / mol, 12 x 10 4 g / mol, 13 x 10 4 g / mol, 14 x 10 4 g / mol, 15 x 10 4 g / mol, 16 x 10 4 g / mol, 17 x 10 4 g / mol, 18 x 10 4 g / mol, 19 x 10 4 g / mol, or 20 x 10 4 g / mol.

[0031] In some embodiments, the weight average molecular weight of the polyacrylonitrile is 20 x 10 4 - 40 x 10 4 g / mol.

[0032] Specifically, the weight average molecular weight of the polyacrylonitrile includes but is not limited to 20 x 10 4 g / mol, 23 x 10 4 g / mol, 26 x 10 4 g / mol, 29 x 10 4 g / mol, 32 x 10 4 g / mol, 35 x 10 4 g / mol, 38 x 10 4 g / mol, or 40 x 10 4 g / mol.

[0033] In some embodiments, the polythiourethane includes a polymer formed by participation of a diisocyanate compound and a thiol compound in polymerization.

[0034] In some embodiments, the molar ratio of the isocyanate group of the diisocyanate compound to the mercapto group of the thiol compound is 1:0.95-1:1.1.

[0035] Specifically, the molar ratio of the isocyanate group of the diisocyanate compound to the mercapto group of the thiol compound includes but is not limited to 1:0.95, 1:1, or 1:1.1.

[0036] Further, the method for preparing the polythiourethane includes the following steps: The thiol compound is placed in a reaction bottle, and before the reaction, 100-110℃ vacuum drying to remove water. After the temperature is reduced to 45-50℃, ensure that all raw materials are in a molten state, add the diisocyanate compound, mix well, then slowly add the catalyst, and react for 3-5h under a protective atmosphere to obtain a polythiourethane.

[0037] Further, the catalyst includes at least one of dibutyltin dilaurate, stannous octoate, bismuth iso-octoate, dibutyltin dimethoxide, dibutyltin diacetate, and dioctyltin dimaleate.

[0038] The catalyst is added in an amount of 0.2%-1.0% of the molar content of the diisocyanate compound to improve the reaction efficiency of the thiol compound and the diisocyanate compound.

[0039] The protective atmosphere is nitrogen or argon.

[0040] It should be noted that a chain extender can also be added during the preparation of the polythiourethane to further improve the flexibility of the solid-state electrolyte. Specifically, the chain extender includes but is not limited to an alcohol chain extender or an amine chain extender. The alcohol chain extender includes but is not limited to butanediol, hexanediol, glycerol, or trimethylolpropane. The amine chain extender includes but is not limited to 3,3'-dichloro-4,4'-diaminodiphenyl methane (MOCA), ethylenediamine (DA), N,N-dihydroxy(diisopropyl)aniline (HPA), or 2-imidazolidone.

[0041] In some embodiments, the diisocyanate compound includes at least one of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI). And / or, the thiol compound includes at least one of ethylene glycol bimerthiolate (GDMA), trimethylolpropane tris(3-mercaptopropionate) (TTMP), pentaerythritol tetra(3-mercaptopropionate) (PTMP), inositol hexa(mercaptopropionate) (DHMP), and polythiol Capcure 3800.

[0042] In some embodiments, the lithium salt includes at least one of lithium bistrifluoromethanesulfonimide, lithium hexafluorophosphate, lithium difluorobis (oxalate) borate, lithium difluorophosphate, lithium perchlorate, lithium tetrafluorophosphate, lithium difluorophosphate, lithium bistrifluoromethanesulfonimide, lithium hexafluorophosphate, lithium difluorobis (oxalate) borate, and lithium difluorophosphate.

[0043] In another aspect, an embodiment of the present application provides a battery including a solid-state electrolyte film, the solid-state electrolyte film including the solid-state electrolyte as claimed in any one of the above.

[0044] It should be noted that the battery can be a soft pack battery, a cylindrical battery, and a square battery.

[0045] In some embodiments, the thickness of the solid-state electrolyte film is 50-200 μm.

[0046] Specifically, the thickness of the solid-state electrolyte film includes but is not limited to 50 μm, 70 μm, 90 μm, 110 μm, 130 μm, 150 μm, 170 μm, 190 μm, or 200 μm.

[0047] In some embodiments, the method for preparing the solid-state electrolyte film comprises the following steps: The polyacrylonitrile, the polythiourethane, and the lithium salt are dissolved in a solvent to obtain a uniform mixed solution. Then the solution is cast on a silica gel mold plate, left to stand to volatilize the solvent, and then placed in an oven to dry into a film to obtain the solid-state electrolyte film.

[0048] Further, the solvent can be selected from at least one of polar aprotic solvents, including acetonitrile, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), propylene carbonate (PC), ethylene carbonate (EC), tetrahydrofuran (THF), 1,4-dioxane, and γ-butyrolactone (GBL).

[0049] The drying temperature is 30-90℃, and the drying method can use gradient drying, specifically: in the first stage, vacuum drying at 30-40℃ for 4-8h to preliminarily remove most of the solvent; in the second stage, vacuum drying at 70-90℃ for 12-24h to completely remove the residual solvent, avoiding the influence of residual solvent on the ionic conductivity of the electrolyte.

[0050] In some embodiments, inorganic fillers can be added to the solid-state electrolyte film to optimize performance, the inorganic fillers can be selected from lithium ion conductor fillers or insulating inorganic fillers, wherein the lithium ion conductor fillers include at least one of LLZO, LLTO, LAGP, Li3PO4, LiTi2(PO4)3, Li2S, TiS2, and MoS2; the insulating inorganic fillers include at least one of Al2O3, SiO2, TiO2, ZrO2, MgO, ZnO, Si3N4, and AlN; the particle size of the inorganic fillers is 10-200 nm, and the addition amount is 1%-10% of the total mass of the solid-state electrolyte, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0051] The battery further comprises a positive electrode and a negative electrode, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer is arranged on at least one side of the positive electrode current collector, and the positive electrode active material layer comprises a positive electrode active material, a conductive agent, and a binder.

[0052] The positive active material includes at least one of lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium cobaltate (LCO), lithium manganate (LMO), lithium nickelate (LNO), ternary material (NCM, NCA), lithium-rich manganese-based (LMR), lithium nickel manganate (LNMO), lithium vanadium phosphate oxide (Li3V2(PO4)3, LiVOPO4).

[0053] The conductive agent includes at least one of carbon black (such as Ketjen black, acetylene black, superconducting carbon black), graphite (such as natural graphite, artificial graphite), carbon nanotube (such as single-walled carbon nanotube, multi-walled carbon nanotube), graphene, reduced graphene oxide; the addition amount of the conductive agent can be adjusted to 1%-5% of the total mass of the positive active material, for example, 1%, 2%, 3%, 4%, 5%, according to the positive conductive requirement.

[0054] The binder includes at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE); the addition amount of the binder is 2%-5% of the total mass of the positive active material, for example, 2%, 3%, 4%, 5%.

[0055] The negative electrode includes one of graphite negative electrode, silicon-oxygen negative electrode, silicon-carbon negative electrode, silicon negative electrode, tin negative electrode, tin oxide negative electrode, tin alloy negative electrode (Sn-Fe, Sn-Co, Sn-Cu), lithium metal negative electrode, lithium alloy negative electrode (Li-Ag, Li-Al, Li-Sn, Li-Mg, Li-Zn, Li-In, Li-Ga), lithium-free negative electrode.

[0056] The application is further described below by examples.

[0057] The solid-state electrolyte and the battery thereof disclosed in the application are specifically described.

[0058] Example 1 Solid-state electrolyte film Polythiourethane: 210 g of ethylene glycol bimerthiolate was placed in a reaction bottle, and before reaction, vacuum drying was performed at 105°C for 3 h to remove water. After the temperature was reduced to 50°C, 168 g of hexamethylene diisocyanate was added, and after uniform mixing, 0.38 g of di-n-butyltin dilaurate was slowly added. The reaction was carried out under nitrogen protection for 5 h to obtain polythiourethane.

[0059] 4 g of polyacrylonitrile, 3 g of polythiourethane, and 3 g of lithium bis-trifluoromethyl sulfonimide were dissolved in 20 g of acetonitrile, and stirred at 25°C for 6 hours to obtain a uniform mixed solution. Then the solution was cast on a silica gel mold plate, and first placed at 25°C for 24 h to volatilize most of the solvent, and then placed in an oven at 80°C to dry into a film to obtain a solid-state electrolyte film.

[0060] The thickness of the solid electrolyte membrane is 100 pm.

[0061] Preparation of the anode sheet The anode is a lithium metal anode.

[0062] Preparation of the cathode sheet NCM811 (active material), conductive agent (carbon black / CNT), polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, and NMP is added to prepare a cathode slurry. The cathode slurry is coated on an aluminum foil, dried, and a cathode sheet is obtained.

[0063] Preparation of the battery The anode sheet, the cathode sheet, and the solid electrolyte membrane are assembled into a battery.

[0064] Examples 2-20 Examples 2-20 and most of the steps of Example 1 are the same, except that the formulations in Table 1 are used.

[0065] Example 21 Example 21 and most of the steps of Example 1 are the same, except that the molar ratio of hexamethylene diisocyanate to ethylene glycol bimerthiolate is 1:0.95.

[0066] Example 22 Example 22 and most of the steps of Example 1 are the same, except that the molar ratio of hexamethylene diisocyanate to ethylene glycol bimerthiolate is 1:0.9.

[0067] Example 23 Example 23 and most of the steps of Example 1 are the same, except that the molar ratio of hexamethylene diisocyanate to ethylene glycol bimerthiolate is 1:1.1.

[0068] Example 24 Example 24 and most of the steps of Example 1 are the same, except that the molar ratio of hexamethylene diisocyanate to ethylene glycol bimerthiolate is 1:1.2.

[0069] Comparative Examples 1-2 Comparative Examples 1-2 and most of the steps of Example 1 are the same, except that the formulations in Table 1 are used.

[0070] Comparative Example 3 Comparative Example 3 and most of the steps of Example 1 are the same, except that polyurethane is used instead of polythiurethane. The polyurethane is prepared using existing polyurethane synthesis methods with hexamethylene diisocyanate and 1,4-butanediol. The glass transition temperature of the polyurethane is 45°C.

[0071] Table 1 The solid-state electrolyte and battery prepared in the above examples and comparative examples were tested as follows.

[0072] 1. Mechanical property test: tensile test was performed using a universal testing machine. According to the standard of ISO527-2, dumbbell-shaped sample was used, with parallel length of 20 mm, width of 4 mm, and sample thickness of 0.5 mm. The tensile speed was 50 mm / min during the test.

[0073] 2. Ion conductivity test: the prepared polymer solid-state electrolyte film was subjected to ion conductivity test at 25°C. The test method was alternating current impedance method, and the alternating current impedance was measured by an electrochemical workstation, with frequency range from 1000 KHz to 0.01 Hz, and perturbation voltage of 10 mV; ion conductivity data were calculated using the formula σ = L / (R x S), and the results are shown in Table 1. Wherein σ is ion conductivity, L is the thickness of the electrolyte film, R is the resistance value of the electrolyte film, and S is the contact area of the electrolyte film and stainless steel electrode.

[0074] 3. Electrical performance test: under the cycle condition of 25°C, 0.5 C charging to 4.0 V, cutoff current of 0.05 C, discharging to 3.0 V at 1 C, and 300 cycles, the capacity retention rate was recorded.

[0075] The test results are shown in Table 2 below.

[0076] Table 2 As can be seen from the test results of the above examples and comparative examples, when the content of polythiourethane decreases, the tensile strength of the solid-state electrolyte film increases, but the elongation at break decreases. When the content of polythiourethane is lower than 20%, the ion conductivity is low due to the inability to interact with polyacrylonitrile. When the content of polyacrylonitrile increases, the tensile strength of the solid-state electrolyte film increases, and the elongation at break decreases. When the content of polyacrylonitrile is lower than 40% or higher than 60%, the ion conductivity is low due to the inability to synergistically interact with polythiourethane. When other types of isocyanate and mercaptan are used as raw materials to synthesize polythiourethane, the mechanical properties, ion conductivity, and capacity retention rate of the solid-state electrolyte film are all good. When the molecular weight of polyacrylonitrile is lower than 20 x 10 4 g / mol, the mechanical strength of the solid-state electrolyte film is poor; when the molecular weight of polyacrylonitrile is higher than 40 x 10 4When the content of the polyacrylonitrile is less than 10 wt%, the compatibility of the polyacrylonitrile and the polythio urethane is poor, and the ionic conductivity of the solid electrolyte membrane is poor. When the solid electrolyte only uses the polyacrylonitrile and the lithium salt, the elongation at break of the solid electrolyte membrane is low. When the solid electrolyte only uses the polythio urethane and the lithium salt, the mechanical strength of the solid electrolyte membrane is not enough. When the solid electrolyte uses the polyurethane instead of the polythio urethane, the ionic conductivity of the solid electrolyte membrane is relatively low.

[0077] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement and improvement within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A solid electrolyte, characterized in that, The solid electrolyte comprises polysulfuron, polyacrylonitrile, and lithium salt, wherein the polysulfuron comprises thiocarbamate structural units.

2. The solid electrolyte according to claim 1, characterized in that, Based on the total mass of the solid electrolyte as 100%, the solid electrolyte comprises 20%-40% polyurethane, 40%-60% polyacrylonitrile and 20%-40% lithium salt.

3. The solid electrolyte according to claim 1, characterized in that, The glass transition temperature of the polysulfuric ester is 40℃-80℃.

4. The solid electrolyte according to claim 1, characterized in that, The polysulfuron has a weight-average molecular weight of 10 × 10⁻⁶. 4 g / mol - 20 × 10 4 g / mol; And / or, the weight-average molecular weight of the polyacrylonitrile is 20 × 10⁻⁶. 4 g / mol - 40 × 10 4 g / mol.

5. The solid electrolyte according to claim 1, characterized in that, The polythiourethane comprises a polymer formed by the polymerization of diisocyanate compounds and thiol compounds.

6. The solid electrolyte according to claim 5, characterized in that, The molar ratio of the isocyanate group in the diisocyanate compound to the mercapto group in the thiol compound is 1:0.95-1:1.

1.

7. The solid electrolyte according to claim 5, characterized in that, The diisocyanate compounds include at least one of toluene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate; And / or, the thiol compound includes at least one of ethylene glycol dimercaptoacetate, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), inositol hexa(mercaptopropionate), and polythiol Capcure 3800.

8. The solid electrolyte according to claim 1, characterized in that, The lithium salt includes at least one of lithium bis(trifluoromethanesulfonate)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium tetrafluorophosphate, lithium difluorophosphate, lithium bis(oxalate)borate, and lithium di(oxalate)borate.

9. A battery, characterized in that, Includes a solid electrolyte membrane, wherein the solid electrolyte membrane comprises the solid electrolyte as described in any one of claims 1-8.

10. The battery according to claim 9, characterized in that, The thickness of the solid electrolyte membrane is 50 μm-200 μm.

Citation Information

Patent Citations

  • Oxygen-enriched polymer electrolyte as well as preparation method and application thereof

    CN109755643A

  • Core-sheath type composite fiber, nonwoven fabric including the composite fiber and article including the nonwoven fabric

    KR1020260004033A

  • Crosslinked polymer electrolyte compositions

    US20030094599A1

  • Self-repairing polymer solid-state electrolyte based on double-sulfur bonds and preparation method therefor

    WO2022205669A1

Cited By

  • Insulating paint, battery and application

    CN122255857A